2021
DOI: 10.2196/26089
|View full text |Cite
|
Sign up to set email alerts
|

Unfolding the Determinants of COVID-19 Vaccine Acceptance in China

Abstract: Background China is at the forefront of global efforts to develop COVID-19 vaccines and has five fast-tracked candidates at the final-stage, large-scale human clinical trials testing phase. Vaccine-promoting policymaking for public engagement is a prerequisite for social mobilization. However, making an informed and judicious choice is a dilemma for the Chinese government in the vaccine promotion context. Objective In this study, public opinions in Chin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
83
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 96 publications
(92 citation statements)
references
References 64 publications
(30 reference statements)
5
83
0
Order By: Relevance
“…An online (web-based) survey was the most common data collection method applied in the cross-sectional studies in our review, of which: Some studies reported using social media platforms including Facebook, Twitter, and LinkedIn to collect data [ 26 , 38 , 41 , 62 , 72 ]; Some studies reported using specific platforms to upload surveys including crowdsourcing platform Amazon Mechanical Turk (mTurk, Amazon, Seattle, WA, USA) [ 32 , 61 ], computer-assisted web interviewing (CAWI) and computer-assisted telephone interviewing (CATI) [ 34 , 53 ], and Qualtrics (Seattle, WA, USA) [ 47 , 55 ]; One study used an online questionnaire to examine public attitudes towards COVID-19 vaccines in three phases: pre-lockdown, during lockdown, and post lockdown with different participants in every phase [ 41 ], and another study conducted two-wave follow-up online surveys [ 55 ]; One study used an online survey with a semi-structured questionnaire following the snowball sampling technique [ 60 ]; One study used open-ended questions to ask about the factors influencing attitudes towards vaccines [ 47 ]; One study used an Internet survey and telephone interviews [ 35 ]; One study used a face-to-face-administered questionnaire [ 37 ]. …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…An online (web-based) survey was the most common data collection method applied in the cross-sectional studies in our review, of which: Some studies reported using social media platforms including Facebook, Twitter, and LinkedIn to collect data [ 26 , 38 , 41 , 62 , 72 ]; Some studies reported using specific platforms to upload surveys including crowdsourcing platform Amazon Mechanical Turk (mTurk, Amazon, Seattle, WA, USA) [ 32 , 61 ], computer-assisted web interviewing (CAWI) and computer-assisted telephone interviewing (CATI) [ 34 , 53 ], and Qualtrics (Seattle, WA, USA) [ 47 , 55 ]; One study used an online questionnaire to examine public attitudes towards COVID-19 vaccines in three phases: pre-lockdown, during lockdown, and post lockdown with different participants in every phase [ 41 ], and another study conducted two-wave follow-up online surveys [ 55 ]; One study used an online survey with a semi-structured questionnaire following the snowball sampling technique [ 60 ]; One study used open-ended questions to ask about the factors influencing attitudes towards vaccines [ 47 ]; One study used an Internet survey and telephone interviews [ 35 ]; One study used a face-to-face-administered questionnaire [ 37 ]. …”
Section: Resultsmentioning
confidence: 99%
“…Some studies reported using social media platforms including Facebook, Twitter, and LinkedIn to collect data [ 26 , 38 , 41 , 62 , 72 ];…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations